Pengelolaan Dream Island Sebagai Daya Tarik Wisata Pantai, Di Mertasari, Desa Sanur Kauh, Kecamatan Badung, Bali - Martha Edlyn Marintan Hutagalung; Dian Pramita Sugiarti (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
This research have a purpose for to know about the management system and condition of 4A (Atraction, Accesibility, Amenity and Anciliary) from the Tourist Attraction of Dream Island Beach. The qualitative Method with the data sources from primary data and secondary data used to collect data. The Primary data of this research is the data that was come from the observation and interview, while the secondary one come from documentary or literature study to complete the primary data. The technique to choose the informant that was being used is Purpose Sampling. The result of this research pointed that the management system of Dream Island Beach didn’t went smoothly, because the planning system not reach the maximum point. The organization system already went smoothly, and all of the staff already put on their position according to their responsibility over their task. The connection between manager and the staff already on good terms, and the condition of tourist attraction on this beach already in good terms with many attraction inside the beach. The accessibility on this tourist destination still need more improvements especially on Toilet whom inadequate. The Anciliary or the institution on the Dream Island beach already reach the average point. Keywords: Management, Dream Island Beach, Beach Tourism.